THE URGENCY OF MARRIAGE REGISTRATION IN THE PERSPECTIVE OF INDONESIAN MARRIAGE LAW AND ISLAMIC LAW - Sulfian, A. Sultan (Institut Agama Islam Negeri Bone, 2023)
This research aims to analyze and explain the urgency of registering marriages in the perspective of Indonesian marriage law and Islamic law, as well as the legal consequences of marriages that are not registered according to Indonesian marriage law and Islamic law. This research is a normative legal research or doctrinal legal research (doctrinal approach), namely legal research that uses secondary data sources which are carried out by approaching legal norms or substances, legal principles, legal theory, legal arguments and legal comparisons with data collection techniques, namely through careful observation and tracing of various legal materials, namely tracing primary legal materials, secondary legal materials, and tertiary legal materials.The results of this research show that the urgency of registering the marriage can be seen from various perspectives. Even though there is still ambiguity regarding the provisions for registering marriages in the Marriage Law, the requirement for registration of marriages is intended within the framework of the state's function of providing guarantees of protection and legal certainty. Meanwhile, from the perspective of Islamic law, the registration of marriages has reached a